Self-Efficacy Mediating the Influence of Social Support on Interest in Continuing Higher Education - Sukron Makmun; Mustari Mustari; Imam Suyitno; Ahmad Jamalong; Najamuddin Najamuddin; Romansyah Sahabuddin (Universitas Muhammadiyah Mataram, 2025)
Developing superior human resources through higher education is crucial for national progress. However, interest in pursuing higher education in West Nusa Tenggara (NTB), particularly Central Lombok, remains a challenge that requires empirical study. This study aims to examine the impact of social support on interest in pursuing higher education, as well as the mediating role of self-efficacy in this relationship. This quantitative study, using a survey approach, involved 100 active university students in Central Lombok Regency as a sample, selected using a simple random sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modelling - Partial Least Square (SEM-PLS). The results showed that social support had a positive and significant effect on interest in pursuing higher education and self-efficacy. A key finding was that self-efficacy fully mediated the effect of social support on interest in pursuing higher education (R2 = 60.9%). Theoretically, this indicates that social support must first be internalized into self-efficacy to effectively increase interest. Policy implications highlight the importance of intervention programs that not only provide social support, but also strategically focus on strengthening individual self-efficacy to encourage higher education participation in the region.